The Fe-Zn Isotopic Characteristics and Fractionation Models: Implications for the Genesis of the Zhaxikang Sb-Pb-Zn-Ag Deposit in Southern Tibet. (20th March 2018) - Wang, Da; Zheng, Youye; Mathur, Ryan; Wu, Song
Abstract : The genesis of the Zhaxikang Sb-Pb-Zn-Ag deposit remains controversial. Three different geological environments have been proposed to model mineralization: a hot spring, a magmatic-hydrothermal fluid, and a sedimentary exhalative (SEDEX) overprinted by a hot spring. Here, we present the electron probe microanalysis (EPMA) and Fe-Zn isotopic data (microsampled) of four samples from the first pulse of mineralization that show annular textures to constrain ore genesis. The Zn/Cd ratios from the EPMA data of sphalerite range from 296 to 399 and overlap the range of exhalative systems. The δ 56 Fe values of Mn-Fe carbonate and δ 66 Zn values of sphalerite gradually decrease from early to late stages in three samples. A combination of the EPMA and isotopic data shows the Fe-Zn contents also have different correlations with δ 66 Zn values in sphalerite from these samples. Rayleigh distillation models this isotope and concentration data with the cause of fractionation related to vapour-liquid partitioning and mineral precipitation. In order to verify this Rayleigh distillation model, we combine our Fe-Zn isotopic data with those from previous studies to establish 12 Fe-Zn isotopic fractionation models. These fractionation models indicate the δ 56 Fe i and δ 66 Zn i values (initial Fe-Zn isotopic compositions) of the ore-forming system are in the range of- 0.5 ‰​ ​ −1 ‰ and- 0 . 28 ‰ ​ 0 ‰, respectively. To conclude, the EPMA data, Fe-Zn isotopic characteristics, and fractionation models support the SEDEX model for the first pulse of mineralization.